Surveillance of strangles in UK horses between 2015 and 2019 based on laboratory detection of Streptococcus equi. (27th September 2021) - McGlennon, Abigail; Waller, Andrew; Verheyen, Kristien; Slater, Josh; Grewar, John; Aanensen, David; Newton, Richard
Abstract: Background: Previously national surveillance data for monitoring strangles ( Streptococcus equi infection) in UK horses was limited. Improved awareness and knowledge of positive diagnoses would permit the optimisation of biosecurity protocols, decreasing the prevalence of strangles. Methods: Seven UK laboratories reported positive strangles diagnoses between 1 January 2015 and 31 December 2019 based on identifying Streptococcus equi via agent detection assays from field‐based practitioner‐submitted samples. Associated clinical history and animal signalment were collected where provided, and descriptive analysis undertaken. Results: Within the study period, 1617 laboratory‐confirmed diagnoses occurred from samples submitted by 315 veterinary practices. Of these, 51.6% were swabs and 44.0% guttural pouch lavages. Diagnoses were primarily based on qPCR alone (59.6%), qPCR and culture (35.8%), or culture alone (4.6%). A total of 1791 clinical signs were reported for 713 diagnoses, where nasal discharge (31.3%) and pyrexia (20.5%) were most frequently reported. Regions with the highest number of diagnoses included North Yorkshire ( n  = 75, 4.6%), Staffordshire ( n  = 71, 4.4%) and West Sussex (North East) ( n  = 63, 3.9%). Conclusion: This study presents important insights into the diagnosis and clinical features of strangles in UK horses, even though limited and/or missing clinical history and signalment on laboratory submission forms restricts the completeness of the data.